Level of Physical Conditions of Football School Players, Batara Jaya Club, Sidomulyo Village, Lirik District, Indragiri Hulu Regency - Fahmi Revaldi Prayoga; Merlina Sari (Jurnal Olahraga Indragiri, 2023)
The purpose of this study was to determine the level of physical condition of the Batara Jaya Football Club Players in Sidomulyo Village, Lirik District, Indragiri Hulu Regency. The type of this research is descriptive. The population and sample in this study were 10 players from Batara Jaya Football Club, Sidomulyo Village, Lirik District, Indragiri Hulu Regency. The research instrument used was a physical condition test for soccer players, namely the leg dynamometer test, the 30 meter run test, the sit and reach test, the shuttle run test, the vertical jump test, and the 15 minute run test. The data analysis technique used is to calculate the category of physical condition values. Based on the results of calculating the average value of the physical condition that has been carried out on the players it is known that the Physical Condition Level of the Players of the Batara Jaya Football Club Football School, Sidomulyo Village, Lirik District, Indragiri Hulu Regency which is owned is 3.2 which belongs to the Less Once category.